The Effect of Minor Additions of Be on the Microstructure of AlSi5Cu2Mg Alloys - Bolibruchova, D.; Sýkorová, M.; Matejka, M.; Chalupova, M. (Archives of Foundry Engineering, 2026)
In this work, the effect of minor additions of Be as an alloying element on the structural properties of the low-silicon AlSi5Cu2Mg alloy was investigated. The aim was to implement a non-standard addition to the AlSi5Cu2Mg alloy, which would lead to an improvement in mechanical properties, mainly elongation, carried out crystallization and stabilize intermetallic phases of the preparation. The results show that Be additions in the range of 0.05 wt. %, 0.08 wt. % and 0.12 wt.% in the low-silicon AlSi5Cu2Mg alloy affect crystallization by refining the grain size and affecting the structural integrity of undesirable iron-rich phases. Be acts as a grain refiner in low-silicon AlSi5Cu2Mg alloys, refining α-(Al). Be had a significant effect on the shape, size and morphology of the intermetallic phases. Compact skeletal Fe-based phases were destabilized and fragmented into Chinese-character particles and fine spherical particles. The change contributed to the improvement of mechanical properties and reduced the degradation effect of the Fe plate phases. The refining effect increased with higher Be addition. This refining significantly improved tensile strength (Rm) and elongation (A50), with the strongest effect at 0.12 wt. % Be. The separate melting and the addition of AlBe5 in the liquid state were shown to be effective and correct.